Phase 2 trial of erlotinib combined with cisplatin and radiotherapy in patients with locally advanced cervical cancer. Issue 8 (10th March 2014) - Nogueira‐Rodrigues, Angelica; Moralez, Giulliana; Grazziotin, Rachele; Carmo, Claudio C.; Small, Isabele A.; Alves, Flavia V.G.; Mamede, Marcelo; Erlich, Felipe; Viegas, Celia; Triginelli, Sergio A.; Ferreira, Carlos G.
Abstract : BACKGROUND: Cisplatin‐based chemoradiation (CRT) is the standard treatment for patients with locally advanced cervical cancer. Epidermal growth factor receptor (EGFR) is frequently overexpressed in cervical cancer, and EGFR inhibition itself has antitumor effects and potentiates CRT. Results of a previous phase 1 trial of the EGFR inhibitor erlotinib combined with cisplatin‐based CRT (E + CRT) recommended a phase 2 erlotinib dose of 150 mg/day. METHODS: Eligibility criteria included International Federation of Gynecology and Obstetrics stage IIB to IIIB epidermoid cervical cancer, no prior therapy, and an Eastern Cooperative Oncology Group performance status of 0 to 2. Patients received erlotinib at a dose of 150 mg/day 1 week before and in combination with cisplatin (40 mg/m 2 administered weekly for 5 cycles) and radiotherapy (4500 centigrays in 25 fractions), followed by brachytherapy (4 fractions at a dose of 600 centigrays weekly). RESULTS: A total of 36 patients completed treatment with E + CRT. The median duration of therapy was 77 days and the median follow‐up period was 59.3 months. The therapy was well tolerated overall, and 34 patients (94.4%) achieved a complete response. The 2‐year and 3‐year cumulative overall and progression‐free survival rates were 91.7% and 80.6% and 80% and 73.8%, respectively. CONCLUSIONS: Treatment with E + CRT appears to be safe and exerts significant activity against locally advanced cervical cancer. To the best of the authors' knowledge, this is the first study to date to demonstrate that a target agent has promising activity against locally advanced cervical cancer. Cancer 2014;120:1187–1193 . © 2014 American Cancer Society . Abstract : According to this phase 2 trial, erlotinib combined with chemoradiation is safe and exerts significant activity in patients with locally advanced cervical cancer. To the best of the authors' knowledge, this is the first study to date to demonstrate that a target agent has promising activity in this disease.